(3CSeGA GdfHi Udi Gddg Ydjg hSde hTQMgGs - (3Jbj GdOjf YHO GdQMef Hf YHO GdeMSf Hf YeQ GdhGSWj GdCfUGQj, YHO GdQMef GdhGSWj,J (B744 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi QaY efGQ GdESdGe HEQSGd eMeO Ydjg hYdi Bdg CaVd GdUdGI hGdSdGe s
(3BNQgG (B:s
(3BNQg hGdMeO ddg QH GdYGdejfq s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B314 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B98s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B90s
(3JHUQGJ GdCUd (B:s
(3HgG NQe s
(3MGdI GdfSNI LjOI s
Keywords: (3GdJGQjNs